2017
DOI: 10.1371/journal.pone.0169888
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Antioxidant System in Fish Hepatopancreas and Intestine Affected by Choline Deficiency: Different Change Patterns of Varied Antioxidant Enzyme Genes and Nrf2 Signaling Factors

Abstract: The liver and intestine are susceptible to the oxidative damage which could result in several diseases. Choline deficiency induced oxidative damage in rat liver cells. Thus, this study aimed to investigate the potential molecular mechanisms responsible for choline deficiency-induced oxidative damage. Juvenile Jian carp were fed diets differing in choline content [165 (deficient group), 310, 607, 896, 1167 and 1820 mg/kg diet] respectively for 65 days. Oxidative damage, antioxidant enzyme activities and related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 70 publications
2
22
0
Order By: Relevance
“…In the present study, the mRNA levels of CuZnSOD, MnSOD, CAT, GST, GR and GPx were all up‐regulated by certain VC supplement, reinforcing the enhanced enzyme activities to some extent. Although performance of gene expression might be inconsistent in different tissues responded to the same nutrient (Wu et al, , ), the present results in liver and intestine were in agreement with the results in gill, spleen and head kidney of grass carp (Xu et al, , ). However, in rat liver, VC did not regulate CuZnSOD and CAT genes expression, but increased activities of CuZnSOD and CAT (Sadi, Yilmaz, & Güray, ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, the mRNA levels of CuZnSOD, MnSOD, CAT, GST, GR and GPx were all up‐regulated by certain VC supplement, reinforcing the enhanced enzyme activities to some extent. Although performance of gene expression might be inconsistent in different tissues responded to the same nutrient (Wu et al, , ), the present results in liver and intestine were in agreement with the results in gill, spleen and head kidney of grass carp (Xu et al, , ). However, in rat liver, VC did not regulate CuZnSOD and CAT genes expression, but increased activities of CuZnSOD and CAT (Sadi, Yilmaz, & Güray, ).…”
Section: Discussionsupporting
confidence: 91%
“…SOD, CAT, GPx and GST are endogenous antioxidants, virtually distributed in all tissues of vertebrates and were widely detected to reflect resistance to oxidation (Wu et al, ; Xu et al, ; Zhang, Shen, Wang, Wu, & Xue, ). The liver and intestine play important roles in metabolism and absorption and are closely related to organism health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the feeding experiment, CAT and SOD were stimulated in animals feeding on leaves treated with a high concentration of AgNPs at 10 °C (Figure 2A, C), suggesting increased intracellular accumulation of ROS. The raised GST activity observed in the animals feeding on leaves treated with the higher AgNP concentration at 16 °C (Figure 2E) further indicated that animals were under oxidative stress (Wu et al 2017). A higher GST activity implies a greater detoxification capacity or conjugation of oxidative products.…”
Section: Discussionmentioning
confidence: 66%